PRANK AS MONEY FETISHISM, CRITICISM OF YOUTUBER CELEBRITIES - Mukhijab, Mukhijab; Noor, As Martadani (POPULIKA, 2023)
Research on strategic artists makes YouTubers a medium for monetizing their content creations. The research method applies critical content analysis to read narratives in prank video content on channels owned by Rans Entertainment (Rafi-Nagita), and Kanal Baim-Paula (Baim Wong-Paula Verhoven). In reading and interpreting prank narratives and social contexts, a political economy perspective with the theory of commodification and money fetishism becomes the analytical knife. The results of this research, Baim-Paula makes prank content with various topics of money. The objects are family members, workers and certain community members. They were tricked (surprised, scared, seduced, helped, entertained by an orchestra), and finally the victims were given gifts. While the victims of pranks from Rafi- Nagita, family and workers. The narrative shocks and "hurts" the victim, but is ultimately happy with the good news. Baim-Paula and Raffi-Nagita put aside ethical problems in content production. The orientation is that successful prank content is controversial in the eyes of the victim and is consumed by many viewers, and adds more and more subscribers. This means that money is the purpose of prank production. Because of that they make prank as a profession.more subscribers. Keywords: You Tuber, Prank, Money.